PENGARUH KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN DI UD. ANALISA KABUPATEN NIAS BARAT - Gulo, Baskem Baru (Universitas Nias Raya, 2025)
This research aims to determine the effect of product quality on consumer satisfaction at UD. Analysis of Mandrehe District, West Nias Regency. The type of research used in this research is quantitative research that is causal in nature. The population and sample used in this research were 42 consumers. The analytical method that will be used to test the hypothesis used in this research is simple linear regression analysis. The results of this research show that product quality has a positive and significant effect on UD consumer satisfaction. Analysis of West Nias Regency, this can be shown by the value of tcount (4.226) > ttable (1.683) and a significant value of 0.000 < 0.05. Based on the results of this research and the discussion that has been described, it can be concluded that product quality influences consumer satisfaction at UD. Analysis of West Nias Regency. The suggestion in this research is, so that consumers remain loyal, UD. The analysis pays attention to the quality of a product to be sold and so that consumers are satisfied when making a purchase, UD. Analysis pays attention to and maintains the level of durability of a product being sold.